Intracellular C3 prevents hepatic steatosis by promoting autophagy and very‐low‐density lipoprotein secretion. Issue 12 (11th November 2021) - Li, Yinling; Sha, Yeqin; Wang, Haitao; He, Lianping; Li, Longjun; Wen, Shuang; Sheng, Liang; Hu, Weiguo; Zhou, Hong
Abstract: Complement component C3, mainly synthesized by hepatocytes, acts as the convergence point of three different pathways in activating the complement cascade. Besides its well‐established roles in the extracellular milieu, C3 performs various intracellular functions such as immunomodulation and pathogen recognition. Although C3 is present at extremely high concentrations in hepatocytes, little is known about its intrahepatic function. In this study, we found that C3 knockout ( C3 −/− ) mice displayed accelerated hepatic triglyceride (TG) accumulation compared with C57BL/6J wild type mice. Mechanistically, C3 deficiency impaired lipophagy in hepatocytes, owing to the disrupted interaction between C3 and autophagy‐related 16 like 1, which is essential for autolysosome assembly. Furthermore, lipophagy deficiency affected the function of the endoplasmic reticulum in C3 −/− mice, subsequently affecting the expression of protein disulfide isomerase and activity of microsomal TG transfer protein, and ultimately impairing the production of hepatic very‐low‐density lipoproteins (VLDLs). Rapamycin and thapsigargin treatment accelerated VLDL secretion and alleviated hepatic lipid accumulation in C3 −/− mice. Our study demonstrates that C3 promotes lipophagy to facilitate VLDL secretion in hepatocytes, thus playing an essential role in balancing TG levels in the liver.